One day of overfeeding impairs nocturnal glucose but not fatty acid homeostasis in overweight men. (10th September 2013) - Magkos, Faidon; Smith, Gordon I.; Reeds, Dominic N.; Okunade, Adewole; Patterson, Bruce W.; Mittendorfer, Bettina
<x xml:space="preserve">Abstract</x> Objective Overfeeding is associated with insulin resistance. Studies on animals suggest this is likely due to disruption of fatty acid metabolism and increased plasma free fatty acid (FFA) availability during the night. We tested the hypothesis that overfeeding induces insulin resistance and increases nocturnal but not daytime plasma FFA availability in human subjects. Design and Methods We measured plasma glucose, insulin, and FFA concentrations hourly for 24 h during a day of isocaloric feeding and a day of hypercaloric feeding (30% calorie excess) in 8 overweight and obese, nondiabetic men (age: 38±3 years; body mass index: 34±2 kg/m2). Results Overfeeding had no effect on daytime plasma glucose, insulin, and FFA concentrations compared to isocaloric feeding, but increased nocturnal glucose (P = 0.007) and insulin (P = 0.003) concentrations and decreased nocturnal FFA concentration (P = 0.006). The homeostasis model assessment of insulin resistance score was ∼30% greater the morning after hypercaloric than isocaloric feeding (P = 0.040). Conclusions One day of overfeeding has no effect on daytime plasma glucose and FFA concentrations but increases nocturnal plasma glucose and insulin concentrations, whereas nocturnal plasma FFA availability is reduced. The acute overfeeding‐induced development of insulin resistant glucose metabolism therefore does not appear to be directly mediated by plasma FFA availability.